2016
DOI: 10.1002/14651858.cd010263.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for alleviating pain during orthodontic treatment

Abstract: Non-pharmacological interventions for alleviating pain during orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 55 publications
0
42
0
8
Order By: Relevance
“…However, a recent database search revealed that the quality of evidence for non-pharmacological interventions to manage orthodontic pain was very low. Further prospective research with long follow-up is required [ 24 ].…”
Section: Literature Review/ Discussionmentioning
confidence: 99%
“…However, a recent database search revealed that the quality of evidence for non-pharmacological interventions to manage orthodontic pain was very low. Further prospective research with long follow-up is required [ 24 ].…”
Section: Literature Review/ Discussionmentioning
confidence: 99%
“…There are several laboratory reports on the ability of PBM treatments to promote craniofacial regeneration in endodontics, periodontics, and implant dentistry involving pulp–dentin, bone, periodontal ligaments, and gingiva. Other areas receiving much attention for the use of light‐based treatments combining two aspects of alleviating pain inflammation and promoting tissue healing and regeneration such as distraction osteogenesis, medication (bisphosphonate)‐related osteonecrosis of the jaws, and accelerated tooth movements (Chiari, ; Fleming et al., ; Vescovi & Nammour, ).…”
Section: Photobiomodulation Therapy In Oral Diseasesmentioning
confidence: 99%
“…Elles s'intéressent à une INM pour traiter un problème de santé commep ar exemple le MBSRe nc omplément des traitements biologiques d'un cancerd us ein [17]. Elles peuvent inclure plusieurs INM pour soigner un problème de santé,p ar exemple la douleur [18], la fatigue durant les traitements du cancer du sein [19], les troubles dépressifs [20], les troubles du sommeil [21], la prévention des rechutesd ' é pisodes dépressifs [22]. Ces méta-analyses peuvent s'intéresser à des indicateurs économiques par exemple les INM ayant le meilleur rapport coûts-efficacité dans le traitement des lombalgies [23], de l'arthrose du genou [24] ou des troubles du sommeil [25].…”
Section: Des Protocoles D'étude Interventionnelle Sur Les Inm Plus Riunclassified